2013
DOI: 10.1162/rest_a_00331
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gasoline Prices on Household Location

Abstract: By raising commuting costs, an increase in gasoline prices should reduce the demand for housing in areas far from employment centers relative to locations closer to jobs. Using annual panel data on a large number of postal codes and municipalities from 1981 to 2008, we find that a 10% increase in gas prices leads to a 10% decrease in construction in locations with a long average commute relative to other locations but to no significant change in house prices. Thus, the supply response prevents the change in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…The secular changes are that the percentages of movers relocating closer to work/school and for convenience to their job increase in the study period while prices are increasing. Our speculation is supported by the findings in existing studies that found gasoline prices have statistically significant effects on household locations within three years of the move (e.g., Molloy and Shan 2013). However, the threshold of the time lag should be further investigated in future research.…”
Section: Methodssupporting
confidence: 83%
“…The secular changes are that the percentages of movers relocating closer to work/school and for convenience to their job increase in the study period while prices are increasing. Our speculation is supported by the findings in existing studies that found gasoline prices have statistically significant effects on household locations within three years of the move (e.g., Molloy and Shan 2013). However, the threshold of the time lag should be further investigated in future research.…”
Section: Methodssupporting
confidence: 83%
“…This article presents evidence overturning in part and extending in part the results of Molloy and Shan (), which leverages similar variation and assumptions about gas price expectations to study housing supply . Molloy and Shan use a discrete difference‐in‐differences model to assess the impact of gasoline prices on real estate prices for especially long‐duration commutes, whereas I focus on a continuous measure of distance.…”
Section: Introductionsupporting
confidence: 54%
“…Nevertheless, an expansion could still affect housing prices via its impact on housing supply, a critique raised by Molloy and Shan (2013) in the literature measuring the impact of gasoline prices on house prices. If HDB constructs more apartments in affected areas in expectation of increased demand, the increase in housing supply will mitigate the expansion price effect.…”
Section: Modelmentioning
confidence: 99%